Ethics and health care quality: an inseparable pairing - Luna Orosco E., Javier (Acta Bioethica, 2011)
By interpreting that beneficence principle is the ethical foundation and that its application is not possible without structural conditions and quality functions, this article establish the inseparable relation between ethics and quality in health care services functioning; furthermore, it develops quality determining factors for good benefits and instruments for verifying and measuring their practice and fulfillment.